Kritik Sastra : Cara Menafsirkan dan Menghargai Karya Sastra - ibadallah, akhmad lendra (Maliki Interdisciplinary Journal, 2025)
Literary criticism can help readers to see the relationship between literary works and the social, cultural and historical context in which they were created. Therefore, literary criticism functions as a tool for understanding and disseminating diversity and complexity in the world of literature, not only as a means for teaching literary teachings. Apart from that, literary criticism can also broaden readers' understanding of various themes and messages conveyed through literary works, as well as help in appreciating the artistic value and beauty contained in each literary work. Thus, literary criticism not only helps readers to understand the context behind literary works, but also to explore the deeper and more complex meaning of each work. Through literary criticism, readers can discover the universal values ​​contained in literary works, as well as appreciate the uniqueness and cultural richness reflected in every word and sentence. Thus, literary criticism is not only a window that leads to a broader understanding of the world of literature, but also a mirror for the diversity and complexity of humans and life. Analyzing literary criticism, readers see how the author uses language and narrative structure to convey relevant messages, provide room for interpretation, and understand the complexity of humans and life. Through literary criticism, readers can explore various points of view and deepen their understanding of the values ​​contained in a literary work. By understanding how the author uses words and sentences to create meaning, readers can feel the cultural richness reflected in every detail of the story. Literary criticism also allows readers to put themselves in the author's position, so they can better appreciate the creative process and human complexity revealed in each literary work.